Calidad biológica y fisicoquímica de tres fuentes de agua y su relación con el fenómeno de El Niño y La Niña (2019)
In the municipality of El Carmen de Viboral, Antioquia, the basin of the La Cimarronas stream and its tributaries Los Andes and La Madera, are the main sources of supply of the local aqueduct. In addition, of these, other five sampling stations located in the upper part of the basin and its tributaries, the physico-chemical, microbiological and biological evaluation was carried out through the use of aquatic macroinvertebrates in three periods of the El Niño hydrological cycle (2016), which were compared with three samplings of the La Niña cycle (2011). The capacity of environmental resilience could be identified under a deficit and excess precipitation of the aquatic system. During the cycle affected by El Niño there was a higher concentration of dissolved oxygen, circumneutral pH, lower water temperature and higher concentrations of nitrites, ammonia nitrogen and total coliforms. During the cycle affected by La Niña, there was a higher water temperature, total solids, hardness, nitrates, total phosphorus and better conditions of biological water quality according to the BMWP index. There were no statistically significant variations in flow, water temperature, electrical conductivity and community indices (diversity, equity, dominance and richness).